The literary underground in the 1660s : Andrew Marvell, George Wither, Ralph Wallis, and the world of restoration satire and pamphleteering - Bardle, Stephen, 1981- (Oxford : Oxford University Press, 2012)
'The Literary Underground in the 1660s' sheds new light on a world of political opposition and sedition. It tells the story of three oppositional writers, Andrew Marvell, George Wither and Ralph Wallis, and their contributions to the restoration literary underground.
Includes bibliographical references.
Description based on print version record.
Keywords: Marvell, Andrew, -- 1621-1678 -- Criticism and interpretation; Wither, George, -- 1588-1667 -- Criticism and interpretation; Wallis, Ralph, -- d. 1669 -- Criticism and interpretation; English literature -- Early modern, 1500-1700 -- History and criticism; Political satire, English -- Early works to 1800.; Pamphleteers -- Great Britain -- History -- 17th century; Radicalism in literature; Great Britain -- Intellectual life -- 17th century